Using imperialist competitive algorithm to find the optimum shape design of internally pressurized torispherical dome ends based on buckling pressure - Abdi, Behzad (Computer Science Journals, 2010)
In this paper, Imperialist Competitive Algorithm (ICA) and Genetic Algorithm (GA)are used to find the optimal form for torispherical dome ends under internal pressure load. According to fabrication and strength of material requirements, a group of compromised counters are studied. According to ASME Section VIII and BS5500 pressure vessel codes, a reasonable buckling pressure limit is proposed. Four-centered ellipse method is used to describe the geometry of the torispherical dome end that this method is commonly used in engineering drawing. A minimum weight optimization problem based on buckling pressure is studied. Two different size torispherical dome end examples are selected and studied. Imperialist Competitive Algorithm is found to be very efficient and easy to use for the applications, such as torispherical dome end and subjected to internally pressurized loading.